1991
DOI: 10.1144/jm.10.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Ostracods and foraminifera from the Early - Middle Eocene of Qeren Sartaba, Jordan Valley

Abstract: -23 species of ostracods and 20 species and species groups of planktonic foraminifera from the 80m thick Qeren Sartabasection, central Jordan Valley, are described and illustrated. The material is determined by planktonic foraminifera1 biostratigraphy to belong to the latest Early Eocene (upper part of Zone P9) and the early Middle Eocene (Zone P10). The palaeoecology is representative of a pelagic marine shelf, with periodic events of shallowing and hardground formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…ESKER (1968), DONZE et al (1982, SAID-BENZARTI, (1998), 4. HONIGSTEIN t~ 91 ROSENFELD (1995, HONIGSTEIN et al (1991), 5. BASSIOUNI (1970.…”
Section: Paracosta Kefensis-leguminocythereis Lokossaensis (Pl)mentioning
confidence: 99%
“…ESKER (1968), DONZE et al (1982, SAID-BENZARTI, (1998), 4. HONIGSTEIN t~ 91 ROSENFELD (1995, HONIGSTEIN et al (1991), 5. BASSIOUNI (1970.…”
Section: Paracosta Kefensis-leguminocythereis Lokossaensis (Pl)mentioning
confidence: 99%
“…In Jordan, only Reticulina proteros and Protobuntonia nakkadii among the many ostracode taxa Bassiouni (1970) described are in common with the present material. In Israel, a large number of ostracode species was recorded by Honigstein et al (1991Honigstein et al ( , 2002 and Honigstein and Rosenfeld (1995) of which only Parakrithe crolifa and Reticulina proteros have been found in the present study. From West Africa, two species recorded in the present study area were recorded in the internal basins in Mali, Niger and NW Nigeria (Dahomeya alata alata, Buntonia fortunata) and five were recorded in coastal basins in Mauritania, Senegal, Ghana, Ivory Coast, Togo, Benin and SW Nigeria (Dahomeya alata alata, Reticulina sangalkamensis, Buntonia fortunata, Alocopocythere attitogonensis, Leguminocythereis lokossaensis).…”
Section: Paleobiogeographic Distributionmentioning
confidence: 44%
“…1998. Occurrence: Paleocene of east Algeria (Damotte and Fleury, 1987), Paleocene to lower Eocene of Jordan (Bassiouni, 1969a) and Tunisia (Donze et al, 1982;Said-Benzarti, 1998;Van Itterbeeck et al, 2007), Paleocene and middle Eocene of Israel (Honigstein et al, 1991(Honigstein et al, , 2002Honigstein and Rosenfeld, 1995) and upper Paleocene (velascoensis Zone) and lower Eocene of Egypt (Khalifa et al, 1984;Bassiouni and Luger, 1990;Morsi, 1999;Shahin, 2000Shahin, , 2005Morsi and Speijer, 2003;Ismail and Ied, 2005;Morsi and Scheibner, 2009). In the present study, it is found in the upper Paleocene (Thanetian) at Sidi Nasseur.…”
Section: Genus Paracosta Siddiqui 1971mentioning
confidence: 99%
“…The genus seems to have been established throughout the 'Protobuntonia numidica ostracode province' of the Southern Tethys (as defined by Luger, 2003) during the Paleocene-Eocene periods. This is especially so if one takes into account the specimens reported by Honigstein et al (1991) from the lower and middle Eocene of Israel and those illustrated by Bassiouni & Luger (1990) from the upper Paleocene of Southern Egypt (Table 1), although their generic status still has to be confirmed.…”
Section: Distributionmentioning
confidence: 98%